Local human capital formation and optimal FDI. Issue 5 (3rd July 2016) - Asali, Muhammad; Cristobal-Campoamor, Adolfo; Shaked, Avner
ABSTRACT: This paper lends both theoretical and empirical support to the notion of optimal foreign direct investment (FDI) levels. It does so by uncovering an inverted-U-shaped relationship between FDI and human capital formation. The optimality of a particular FDI inflow depends on the educational incentives induced by FDI on the local, heterogeneous population. Our estimates confirm the significance of a positive (linear) and a negative (non-linear) impact of FDI stocks on tertiary schooling, which are exclusively relevant in developing countries.